Intrinsic and extrinsic determinants of central nervous system axon outgrowth into alginate-based anisotropic hydrogels. (November 2015) - Pawar, Kiran; Prang, Peter; Müller, Rainer; Caioni, Massimiliano; Bogdahn, Ulrich; Kunz, Werner; Weidner, Norbert
Graphical abstract: Abstract: Appropriate target reinnervation and functional recovery after spinal cord injury depend on longitudinally directed regrowth of injured axons. Anisotropic alginate-based capillary hydrogels (ACH) support peripheral nervous system derived axon growth, which is accompanied by glial supporting cell migration into the ACH. The aim of the present study was to analyze central nervous system (CNS) derived (entorhinal cortex, spinal cord slice cultures) axon regrowth into ACH containing linearly aligned capillaries of defined capillary sizes without and with gelatin constituent. Anisotropic ACH were prepared by ionotropic gel formation using Ba 2+, Cu 2+, Sr 2+, or Zn 2+ ions resulting in gels with average capillary diameters of 11, 13, 29, and 89 μm, respectively. Postnatal rat entorhinal cortex or spinal cord slice cultures were placed on top of 500 μm thick ACH. Seven days later axon growth and astroglial migration into the ACH were determined. Axon density within capillaries correlated positively with increasing capillary diameters, whereas longitudinally oriented axon outgrowth diminished with increasing capillary diameter. Axons growing into the hydrogels were always accompanied by astrocytes strongly suggesting that respective cells are required to mediate CNS axon elongation into ACH. Overall, midsize capillary diameter ACH appeared to be the best compromise between axon density and orientation. Taken together, ACH promote CNS axon ingrowth, which is determined by the capillary diameter and migration of slice culture derived astroglia into the hydrogel. Statement of Significance: Biomaterials are investigated as therapeutic tools to bridge irreversible lesions following traumatic spinal cord injury. The goal is to develop biomaterials, which promote longitudinally oriented regeneration of as many injured axons as possible as prerequisite for substantial functional recovery. Optimal parameters of the biomaterial have yet to be defined. In the present study we show that increasing capillary diameters within such hydrogels enhanced central nervous system axon regeneration at the expense of longitudinal orientation. Axon ingrowth into the hydrogels was only observed in the presence of glial supporting cells, namely astrocytes. This suggests that alginate-based hydrogels need to be colonized with respective cells in order to facilitate axon ingrowth.